PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK STORE HARDWARE PARAGON MALL SEMARANG - Alfiana Septarini; Sendhang Nurseto (Jurnal Ilmu Administrasi Bisnis, 2018)
Current economic developments encourage of competition in the various business sectors mainly on the same type of business, namely, fashion outlets. The tight of competition makes business bersing each other in boosting sales to obtain the expected pofitabilitas.Therefore, the required efforts to enhance the purchasing decisions ofconsumers. The level of Hardware Store sales experienced a fluctuation in the level of sales. The purpose of this research is to know the extent influence of the price and quality service on the decision purchase at Hardware Store Paragon Mall Semarang. This research type is explanation research with 100 respondent is drawn using the purposeve technique of sampling. Data collection techniques using questionnaires and interviews. Methods of analysis used in this study was the use of regression analysis help software SPSS (Statistical Program for Social Science) version 16. Based on the results of the analysis can be concluded there is a positive and significant influence between the price and quality of service of purchase decisions partially or simultaneously. This has been proven through a simple linear regression test with the value of the regression price affecting the purchase decision of 0.430 and service quality affects the purchasing decisions of 0.507. As for advice to pay attention to the price of Hardware is the Paragon a few items are more expensive than competitors and did training to employees against precision as well as hospitality services to enhance quality of service in Hardware Paragon.